PEMBIAYAAN PERMODALAN IDEAL DALAM MENGATASI PRAKTIK RENTENIR - HARJONI HARJONI; REZA FAHMI (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2018)
The purpose of this study is to examine small Islamic financial institutions in assisting traders in traditional markets of loan shark practices. This research uses descriptive explorative approach. The object of research is traditional traders in Aceh. The conclusions of the study are: 1) Islamic Micro Finance Baitul Qiradh Baiturrahman is easy to provide capital financing and overcome the practice of loan shark. 2) Working capital is channeled using a system of cooperation, where the trader is obliged to return the principal and profit share of the profit. 3) Uncomplicated organizational structure and management pattern will make Islamic Micro Finance BQ Baiturrahman easy to realize. 4) The existence of Islamic Micro Finance BQ Baiturrahman can be an example for other sharia micro finance institutions in strategy management, so that sharia micro finance institution can be the main choice for micro business actors.